Leadership 101 what every leader needs to know - Maxwell, John C. (Thomas Nelson, 2002)
Drawing from John Maxwell's bestsellers Developing the Leader Within You, The 21 Irrefutable Laws of Leadership, The 21 Indispensable Qualities of a Leader, and Becoming a Person of Influence, Leadership 101 explores the timeless principles that have become Dr. Maxwell's trademark style. Maxwell focuses on essential and time-tested qualities necessary for true leadership -influence, integrity, attitude, vision, problem-solving, and self-discipline -and guides readers through practical steps to develop true leadership in their lives and the lives of others.